Talented high school football players` perception of talent identification criteria - Matin, V.; Sæther, A. (SportMont, 2016)
Talent identification (TID) is a major part of top-level football. Even so, most studies of talented players are skewed towards exploring the work of coaches who are already dealing with pre-defined "talented performers" and not a broader range of players, such as high school students in sport specialisation programs (SSP) and elite sport specialisation programs (ESSP). In this study, we explore which skills high school players find most important, how they assess their own skills compared to their schoolmates and which skills their school and club coaches find most important, comparing: girls and boys, an SSP and an ESSP school and players playing top-level versus low-level football. Included in this study were 111 high school football players (81 boys and 30 girls) representing one SSP and one ESSP. The results showed that the players ranked mental and tactical skills as most important compared to the school and club coach who ranked, respectively, technical and physical, and tactical and technical skills as most important. Girls considered both tactical and physical skills significantly ((<0.01) more important than boys. Players from SSP considered mental skills as significantly more important, while the ESSP players considered the tactical skills as significantly more important. Furthermore, the top-level players considered technical and mental skills as significantly more important. These results could indicate that gender, school type and playing level could affect the players` perception of the most important skills in TID.